Implementasi Literasi di Sekolah Dasar - Fahrianur Fahrianur; Ria Monica; Kristia Wawan; Misnawati Misnawati; Alifiah Nurachmana; Syarah Veniaty; Ibnu Yustiya Ramadhan (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of writing this article is to provide information related to the concept of literacy that has been implemented in learning activities in schools. How literacy activities are carried out in accordance with the concept that has been understood and whether the concept of literacy is in accordance with the actual concept. Secondly, this article will also contain information about the understanding of the concept of literacy based on the results of the literature review. In addition, this writing will provide the results of studies and analyses, how the implementation of literacy activities in schools, and how the impact is in improving the literacy skills of students, especially in elementary schools. The writing of this article is based on a literature review and observation results by conducting interviews and direct observation of literacy activities carried out, the data obtained from various sources is then analy kozed and discussed descriptively exploratively. From the data obtained, information is obtained that, there are already literacy activities carried out in elementary schools, literacy activities carried out are in accordance with the concept of literacy, but the main concern is that literacy activities carried out are not optimal and not sustainable, so they are less able to build a culture of literacy in schools.